Pengaruh penerapan Keselamatan dan Kesehatan Kerja (K3) terhadap kinerja pada proyek pembangunan Gedung Laboratorium Terpadu Kemaritiman Universitas Negeri Gorontalo (UNG) - Mael, Trias Melati; Hadi, Abd Karim; Marica, Husni (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The work performance of the Gorontalo State University (UNG) Maritime Integrated Laboratory Building Construction Project can be influenced by labor productivity. To increase labor productivity, it is important to ensure that the workforce remains safe and healthy when carrying out work activities because in construction work there is a lot of risk of injury or accident. fatal if not prevented or addressed will have fatal consequences. This makes the Implementation of Occupational Safety and Health (K3). Occupational Safety and Health (K3) factors for workers that can influence Work Productivity are: Work Safety, Environmental Management, Communication Management, Environmental Monitoring, and Work Mobilization. This is proven to be in accordance with the results of statistical data analysis using the Analysis method. Multiple Regression. From the Occupational Safety and Health (K3) factors for workers that can influence Job Productivity above, which are the most dominant or influential based on the analysis of Multiple Regression results, it can be concluded that the Job Mobilization Factor has a Constant Value of 0.194 which is greater than the Constant Value in Other factors.